Cisto do ducto nasopalatino: relato de caso clínico - Andresevski, Fabrícia Michelon (2024)
The nasopalatine duct cyst is a non-odontogenic, benign cyst, common in the oral cavity and the most frequent of the non-odontogenic cysts of the jaws, containing a prevalence of 1 to 11.6%, located between vital maxillary central incisors. Since it is located in the anterior region of the maxilla, it can interfere with facial aesthetics depending on the severity of each case. It has slow growth, volume increase in the anterior region of the palate, fluid, and asymptomatic, and can even be identified by radiographic findings. The treatment is based on surgical removal, where added to clinical examination and vitality testing, the diagnosis is defined. The aim of this paper is to report a clinical case of a 53-year-old Caucasian woman, who sought treatment without complaint of pain, referred by another dental-surgeon, presenting a cyst in the maxilla region. Imaging exams revealed a radiolucent lesion between the roots of the upper central incisors. Computed tomography showed a cystic lesion in the path of the nasopalatine duct. The vitality test of the teeth involved was positive. The procedure was to perform an excisional biopsy and the material was later sent for histopathological analysis, confirming the clinical hypothesis and the diagnosis was nasopalatine cyst. The patient is currently being monitored.